Antiviral activity of ethanol extract of Lophatherum gracile against respiratory syncytial virus infection. (5th October 2019) - Chen, Li-Feng; Zhong, Yuan-Lin; Luo, Ding; Liu, Zhong; Tang, Wei; Cheng, Wen; Xiong, Si; Li, Yao-Lan; Li, Man-Mei
Abstract: Ethnopharmacological relevance: Lophatherum gracile, an important medicinal plant, is used traditionally in the treatment of cough associated with lung heat and inflammation. In this study, an ethanol extract of L. gracile (DZY) was shown to inhibit respiratory syncytial virus (RSV) infection and RSV-induced inflammation in vitro and in vivo . These findings provide a strong and powerful support for the traditional use of L. gracile in the treatment of RSV-related diseases. Aim of the study: To determine the anti-RSV activities of DZY and its ingredients, and explore the relationship between RSV infection and inflammation. Materials and methods: DZY was extracted from L. gracile and its major ingredients were determined by high-performance liquid chromatography (HPLC). RSV-infected HEp-2 and RAW264.7 cell models were established to assess the inhibitory effect of DZY on RSV replication and nitric oxide (NO) production in vitro . Three-week-old BALB/c mice challenged intranasally with RSV were used to establish RSV-infected animal mode. The mice were respectively administered DZY at high-, middle-, and low-dose in different groups. The anti-RSV activity of DZY was evaluated by detecting viral load, lung lesion, CD4 + and CD8 + T cell population, and interleukin (IL)-1β, tumor necrosis factor (TNF)-α, and interferon (IFN)-γ expression in the lung tissue. Results: In HEp-2 cell line, DZY effectively inhibited RSV infection in a dose-dependent manner with IC50 values of 20 μg/mL against RSV (Long strain) and IC50 values of 25 μg/mL against RSV (A2 strain). The anti-RSV activity of DZY was mainly determined by isoorientin, swertiajaponin, 3, 5-di-caffeoylquinic acid, and 3, 4-di-caffeoylquinic acid. Moreover, DZY suppressed NO production induced by RSV in vitro. In vivo, oral administration of DZY significantly reduced the viral load and ameliorated lesions in the lung tissue. A probable antiviral mechanism was mediated by slightly improving the ratio of CD4 + /CD8 + T cells and inhibiting the mRNA and protein expression of IL-1β, TNF-α, and IFN-γ. Conclusions: (1) DZY exhibits anti-RSV activities both in vitro and in vivo . (2) RSV infection can trigger a series of inflammatory reactions; thus, ameliorating inflammation is helpful to control the course of disease caused by RSV. These findings provide the rationale and scientific evidence behind the extensive use of L. gracile in traditional medicine for the treatment of diseases potentially caused by RSV. Graphical abstract: fx1